2022
DOI: 10.3389/fphar.2022.842671
|View full text |Cite
|
Sign up to set email alerts
|

Wuwei Qingzhuo San Ameliorates Hyperlipidemia in Mice Fed With HFD by Regulating Metabolomics and Intestinal Flora Composition

Abstract: Hyperlipidemia is one of the most common metabolic disorders that threaten people’s health. Wuwei Qingzhuo San (WQS) is a traditional Mongolian medicine prescription, which is widely used in Mongolia for the treatment of hyperlipidemia. Our previous studies found that it has hypolipidemic and hepatoprotective effects on hyperlipidemic hamsters. However, the underlying lipid-lowering mechanisms of WQS and its relationship with intestinal flora are not yet clear. In this study, 16 S rRNA gene sequencing and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This would help analyze the pathogenesis of hyperlipidemia and the mechanism of action of drugs. For example, a metabolomics study found that 12 biomarkers of metabolic disorders showed a trend of regression after treatment with Wuwei Qingzhuo San, suggesting that hyperlipidemia can be improved by improving metabolic disorders [54]. Our study identified eight key metabolites that could serve as potential markers closely associated with hyperlipidemia, including 3-Hydroxypicolinic acid, 4,5-Di-O-caffeoylquinic acid, berberine, betaine, L-Pipecolic acid, Monoethylhexyl phthalic acid, L-Palmitoylcarnitine, and Stearoylethanolamide.…”
Section: Discussionmentioning
confidence: 99%
“…This would help analyze the pathogenesis of hyperlipidemia and the mechanism of action of drugs. For example, a metabolomics study found that 12 biomarkers of metabolic disorders showed a trend of regression after treatment with Wuwei Qingzhuo San, suggesting that hyperlipidemia can be improved by improving metabolic disorders [54]. Our study identified eight key metabolites that could serve as potential markers closely associated with hyperlipidemia, including 3-Hydroxypicolinic acid, 4,5-Di-O-caffeoylquinic acid, berberine, betaine, L-Pipecolic acid, Monoethylhexyl phthalic acid, L-Palmitoylcarnitine, and Stearoylethanolamide.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia is characterized by abnormal lipid levels in the blood and constitutes a potentially harmful disease leading to CVDs with high mortality ( Ge et al, 2022 ). Previous studies found that YL may treat hyperlipidemia by modulating angiogenesis and suppressing inflammatory responses ( Chen et al, 2019 ; Xiao et al, 2023a ).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia is characterized by abnormal lipid levels in the blood and constitutes a potentially harmful disease leading to CVDs with high mortality (Ge et al, 2022). Previous studies found that YL…”
Section: Discussionmentioning
confidence: 99%
“…The control group was fed ordinary feed (containing 18.5% protein, 4.6% fat, 58.9% carbohydrate, 3.2% crude fiber, 6.8% ash, 1.28% calcium, and 0.92 phosphorus), and the other groups were fed HFD for 30 days (containing 22.5% crude protein, 24.2% crude fat, 3.2% crude fiber, 5.6% crude ash, 1.2% calcium, and 0.8% total phosphorus). At week 4, mouse serum was collected to detect the levels of four indicators: TG, TC, LDL-C, and HDL-C ( Li et al, 2022a ; Ge et al, 2022 ). The treatment group was continuously administered TCDCA (25, 50, and 100 mg/kg/day) ( Xu et al, 2023b ) and fenofibrate (50 mg/kg/day) ( Sohn et al, 2017 ) by gavage for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%